The First 500 Registrations to the Research Registry®: Advancing Registration of Under-Registered Study Types - Agha, Riaz; Fowler, Alexander J.; Limb, Christopher; Al Omran, Yasser; Sagoo, Harkiran; Koshy, Kiron; Jafree, Daniyal J.; Anwar, Mohammed Omer; McCullogh, Peter; Orgill, Dennis Paul (Frontiers in Surgery, 2016)
The Declaration of Helsinki 2013 encourages the registration of all research studies involving human participants. However, emphasis has been placed on prospective clinical trials, and it is estimated that only 10% of observational studies are registered. In response, Research Registry® was launched in February 2015; a retrospectively curated registry that is free and easy to use. Research Registry® enables prospective or retrospective registration of studies, including those study types that cannot be registered on existing registries. In this study, we describe the first 500 registrations on Research Registry®. Since the launch of Research Registry® in February 2015, data of registrations have been collected, including type of studies registered, country of origin and data curation activity. Inappropriate registrations, such as duplicates, were identified by the data curation process. These were removed from the database or modified as required. A quality score was assigned for each registration, based on Bradford-Hill’s criteria on what research studies should convey. Changes in quality scores over time were assessed. 500 studies were registered on Research Registry® from February 2015 to October 2015, with a total of 1.7 million patients enrolled. The most common study types were retrospective cohort studies (37.2%), case series (14.8%) and first-in-man case reports (10.4%). Registrations were received from 57 different countries; the most submissions were received from Turkey, followed by China and the United Kingdom. Retrospective data curation identified 80 studies that were initially registered as the incorrect study type, and were subsequently correct. The Kruskal-Wallis test identified a significant improvement in quality scores for registrations from February 2015 to October 2015 (p < 0.0001). Since its conception in February 2015, Research Registry® has established itself as a new registry that is free, easy to use and enables the registration of various study types, including observational studies and first-in man case reports. Going forward, our plan is to continue developing Research Registry® in line with user feedback and usability studies. We plan to further promote Research Registry® to advance the cause of registration of research, to increase compliance with the Declaration of Helsinki 2013.